Modul Pelatihan Peningkatan Self-Efficacy Guru dalam Pembelajaran Siswa Gifted - Nazib Qodarrohman; Eneng Nuraili Wangi (Jurnal Riset Psikologi, 2026)
Abstract. Education is an important pillar of national development, with teachers serving as the main actors in creating quality learning. In inclusive education, teachers are required to be able to teach students with diverse characteristics, including gifted students. However, many teachers still lack confidence in their ability to teach these students, which is related to aspects of competence and self-belief in carrying out their professional roles. This study aims to develop a training module focused on improving teachers’ self-efficacy in teaching gifted students. The research method uses a Research and Development (R&D) approach to develop the training module, as well as a quasi-experimental design with a one-group pretest–posttest model to test the module’s effectiveness. The research sample involved 53 elementary school teachers divided into two stages of trials, namely a preliminary trial and a main trial. The expert judgment results indicated that the training module is valid and feasible to use. Data analysis using a paired t-test showed a significant increase in teachers’ self-efficacy after the training. This study concludes that the developed training module is effective in improving teachers’ self-efficacy and has the potential to enhance the quality of learning for gifted students in Bandung Regency. Abstrak. Pendidikan merupakan pilar penting pembangunan bangsa, dengan guru sebagai aktor utama dalam menciptakan pembelajaran yang berkualitas. Dalam pendidikan inklusif, guru dituntut mampu mengajar siswa dengan beragam karakteristik, termasuk siswa gifted. Namun, masih banyak guru yang kurang yakin terhadap kemampuannya dalam mengajar siswa tersebut, yang berkaitan dengan aspek kompetensi dan keyakinan diri dalam menjalankan peran profesionalnya. Penelitian ini bertujuan untuk menyusun rancangan modul pelatihan yang berfokus pada peningkatan self-efficacy guru dalam pembelajaran siswa gifted. Metode penelitian menggunakan pendekatan Research and Development (R&D) untuk mengembangkan modul pelatihan, serta desain quasi-experimental dengan model one group pretest–posttest untuk menguji efektivitas modul. Sampel penelitian melibatkan 53 guru SD yang terbagi dalam dua tahap uji coba, yaitu uji coba awal dan uji coba utama. Hasil expert judgement menunjukkan bahwa modul pelatihan valid dan layak digunakan. Analisis data menggunakan uji-t berpasangan menunjukkan adanya peningkatan self-efficacy guru secara signifikan setelah pelatihan. Penelitian ini menyimpulkan bahwa modul pelatihan yang dikembangkan efektif dalam meningkatkan self-efficacy guru dan berpotensi meningkatkan kualitas pembelajaran siswa gifted di Kabupaten Bandung.